Nghiên cứu đặc trưng, tính chất và hình thái cấu trúc của hạt tổ hợp polylactic axit/chitosan chế tạo bằng phương pháp vi nhũ - Thu Trang, Nguyễn Thị; Chinh, Nguyễn Thuý; Mai, Trần Thị; Hoàng, Thái (Vietnam Journal of Chemistry, 2016)
Nanocomposites are synthesized on the basis of the polymer with combination of the advantages of each polymer composition. In particular, composites based on polylactic acid (PLA) and chitosan (CS) are increasingly interested in the study due to the good adhesion, the ability biodegradable and biocompatible [1-3]. The PLA/CS nanocomposites can be prepared by emulsion method, solution method or electrospinning method, etc. In this study, the PLA/CS nanoparticles were synthesized by emulsion method. These nanoparticles were characterized by Fourier Transform Infrared (FTIR), Differential Scanning Calorimetry (DSC), Zetasizer and Field Emission Scanning Electron Microscopy (FESEM). The compatibility of PLA and CS was investigated by FTIR and DSC. The effect of the component ratio (PLA/CS) on morphology and size distribution of the nanocomposites was determined by FESEM and Zetasizer. The obtained results showed that the particle size range from 100 nm to 300 nm. Keywords. Polylactic acid, chitosan, polyethylene oxide, polycaprolacton, emulsion.